The Role of Gender in Juvenile Idiopathic Arthritis-Associated Uveitis - Ahmadreza Moradi; Rowayda M. Amin; Jennifer E. Thorne (Journal of Ophthalmology)
Uveitis is a common complication of juvenile idiopathic arthritis (JIA) affecting up to 30% of patients with JIA. Although the typical bilateral chronic anterior uveitis associated with the persistent and extended oligoarticular and polyarticular, rheumatoid factor negative variants of JIA occurs predominantly in girls, boys may be more commonly affected in the HLA-B27 positive, enthesitis variant of JIA. While female gender has been associated with the development of the chronic anterior uveitis in children with JIA, the clinical course of JIA-associated uveitis may be worse in boys than in girls. The purpose of this paper is to review the available published literature to determine the role of gender in the clinical presentation and outcomes of patients with JIA-associated uveitis.